216k views
4 votes
2x + y - z = 3
-x + 2y + 4z = -3
x – 2y - 3z = 4

User Tharsan
by
8.2k points

2 Answers

3 votes

Answer:

x = 3; y = -2; z = 1.

Explanation:

-x + 2y + 4z = -3

x – 2y - 3z = 4

(-x + x) + (2y - 2y) + (4z - 3z) = (-3 + 4)

0 + 0 + z = 1

z = 1

x - 2y - 3(1) = 4

x - 2y - 3 = 4

x - 2y = 7

x = 2y + 7

2(2y + 7) + y - (1) = 3

4y + 14 + y - 1 = 3

5y + 13 = 3

5y = -10

y = -2

x = 2(-2) + 7

x = -4 + 7

x = 3

So, your answer is (3, -2, 1).

Hope this helps!

User Nibir
by
7.9k points
4 votes

Answer:

x=3, y=-2, z=1

Explanation:

I solved by substitution

User Eskwayrd
by
8.4k points